طريق الحج في مصر الإسلامية من الفتح العربي إلي نهاية الدلة الإخشيدية "21 - 358 هـ. / 641 - 969 م." - أحمد، ندى سيد محمد; الشوربجى، أمينة أحمد إمام; رمضان، هويدا عبدالعظيم (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2020)
كان لموقع مصر الجغرافي المتميز أثرا هاما في جعلها تحتل مكانة كبيرة في طرق التجارة الدولية؛ حيث ساهمت طرق مصر البرية والبحرية في أن تكون معبرا للقوافل التجارية والدينية، كما جعلها حلقة من حلقات التواصل الحضاري والثقافي بين بلاد الشرق والغرب، وسوف نحاول في تلك الدراسة أن نلقي الضوء على مدي مساهمة الطرق المصرية في نقل الحجاج المسلمين من مصر وبلاد المغرب العربي، والقارة الإفريقية إلى مكة المكرمة والمدينة المنورة من أجل أداء فريضتي الحج والعمرة، مع بيان الدور الرائد الذي ساهمت به الأسواق المصرية في دعم ومساندة بلاد الحجاز في أوقات الشدة والأزمات الاقتصادية. وكان الحجاج والتجار يسافرون من مصر إلى بلاد الحجاز، باستخدام عدة وسائل وأدوات للنقل، والتي قد صنعت خصيصا من أجل توفير عنصري الأمان والراحة للحجاج، وتعمل على تخفيف مشقة السفر، وقد اختلفت تلك الوسائل باختلاف الطرق الذي يتم السفر عبرها، حيث كانوا يستخدمون الدواب للسفر عبر الطريق البري، والسفن، والمراكب النيلية للسفر عبر الطريق البحري. ولقد حرص الولاة والخلفاء المسلمون على العناية والاهتمام بتلك الطرق، وعملوا على توفير الخدمات المختلفة بها، مثل: مصادر المياه العذبة، والأسواق والاستراحات ووسائل الإنارة وبناء السفن، مع القيام بمحاولة التغلب على كل العقبات التي تواجه المسافرين، مثل: السيول، وأثر تساقطها على الأماكن الدينية، وأثناء أداء الحجاج والمعتمرين لمناسكهم، إلى جانب قيامهم بصد اعتداءات القبائل العربية المستمرة على قوافل التجارة والحج، وامتناعهم عن المشاركة في تأمين الطرق والدفاع عن المسافرين.
Egypt unique geographic location has had a so significant impact on it that it has occupied a great place in the international trade routes. Egypt's land and sea routes have contributed to it having been a passageway for commercial and religious convoys. It also made it a point of civilizational and cultural communication between the countries of the East and the West. In this study, we will try to highlight how the Egyptian routes contributed to transporting Muslim pilgrims from Egypt, the countries of the Maghreb and the African continent to Mecca and Medina to perform the hajj and Umrah, indicating the leading role which the Egyptian market contributed to supporting and sustaining the Hijaz country in times of hardship and economic crises. Pilgrims and traders used to travel from Egypt to Hijaz using several means and tools of transportation which were made especially for providing safety and comfort to pilgrims and they reduced the travel hardship. These means varied depending on the routes used for travelling. They used animals to travel by road and Nile ships and boats to travel by sea. The Muslim rulers and caliphs had interest in and care about those routes. They worked on providing various services to them, such as fresh water sources, markets, rest houses, lighting means, and shipbuilding. They tried to overcome all obstacles facing travelers, such as floods and the impact of their falling on religious places during the pilgrims' performance of rituals. In addition, they repelled the continuous Arab tribes' attacks on trade and pilgrim convoys and their refusal to participate in securing roads and defending travelers.
Keywords: التاريخ الإسلامي -- طرق الحج -- الدولة الإخشيدية -- مصر